Diagnosis of certain diseases and the design of the instrument for it, based on the spectral analysis of human muscles microwaves - Ярочкін, Олександр Вікторович (Technology audit and production reserves, 2012)
The article describes the results of the work on the investigation microwaves of human arms (tremor) and construction of device for their research is proposed. The results are showed and analyzed